2021
DOI: 10.3390/jcm10214825
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer and Fertility-Sparing Treatment

Abstract: Radical hysterectomy with pelvic node dissection is the standard treatment for early-stage cervical cancer. However, the latter can be diagnosed at a young age when patients have not yet achieved their pregnancy plans. Dargent first described the vaginal radical trachelectomy for patients with tumors <2 cm. It has since been described a population of low risk of recurrence: patients with tumors <2 cm, without deep stromal infiltration, without lymphovascular invasion (LVSI), and with negative lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In such cases, in order to preserve the uterus, a simple or radical trachelectomy could then be proposed, as fertility-sparing surgery. 1 2 The size of the tumor and the presence of LVSI are associated with higher risk of relapse 1 2 . The ConCerv trial was recently published and found a rate of recurrence of 3% in patients undergoing a simple cone/trachelectomy with a tumor size < 20 mm without LVSI ( one local recurrence in 31 stage IB1 cases) 3 .…”
Section: Dr Morice: What Would Be the Options To Preserve Fertility I...mentioning
confidence: 99%
See 4 more Smart Citations
“…In such cases, in order to preserve the uterus, a simple or radical trachelectomy could then be proposed, as fertility-sparing surgery. 1 2 The size of the tumor and the presence of LVSI are associated with higher risk of relapse 1 2 . The ConCerv trial was recently published and found a rate of recurrence of 3% in patients undergoing a simple cone/trachelectomy with a tumor size < 20 mm without LVSI ( one local recurrence in 31 stage IB1 cases) 3 .…”
Section: Dr Morice: What Would Be the Options To Preserve Fertility I...mentioning
confidence: 99%
“…The ongoing GOG 278 trial (that includes patients treated with simple cone/trachectomy or simple hysterectomy) will provide information on quality of life in patients undergoing conservative management of early disease (NCT01649089). A relapse rate of 4% and a death rate of approximately 2% have been reported after radical trachelectomy by the vaginal approach 1 2 . However, these ultra-conservative strategies could not be safely proposed in FIGO 2018 stage IB2 disease (with further foci of LVSI) due to significant increase of recurrence.…”
Section: Dr Morice: What Would Be the Options To Preserve Fertility I...mentioning
confidence: 99%
See 3 more Smart Citations